DETERMINANTS OF HOUSEHOLD DECISIONS IN UTILIZING FINANCIAL INSURANCE SERVICES PRODUCTS - Kadek Ayu Santhi Novitasari; Ni Made Tisnawati (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2024)
Economic growth and insurance can create a causal relationship. Insurance is one way that households can use to help provide financial security. The insurance demand function is a representation of the level of insurance penetration. The insurance penetration rate in Indonesia in 2022 will only be 2.82%. The cause of low insurance penetration is low financial literacy, and is supported by household socio-economic characteristics. The aim of this research is to analyze the influence and magnitude of the influence of financial literacy, household income, number of dependents, education level, gender simultaneously and partially on household decisions in utilizing insurance financial service products in Denpasar City. The population in this study were households in Denpasar City. Data collection was carried out by taking a sample of 100 households in Denpasar City using a non-probability sampling technique which is purposive sampling. By using Binary Logistic Regression, the results of this study show that financial literacy, household income, number of dependents, education level and gender simultaneously influence household decisions in utilizing insurance financial service products. financial literacy, Household income, number of dependents, education level, and gender have a significant positive effect on household decisions in utilizing insurance financial service products.